In memoriam Piet Rietveld - Nijkamp, Peter (European Journal of Transport and Infrastructure Research, 2014)
Below you will find an ‘In memoriam’ concerning Piet Rietveld, who until his recent passing away was member of EJTIR’s Editorial Advisory Board (EAB). The In Memoriam is written by Peter Nijkamp, chairman of the EAB. As EAB member, Piet has contributed to EJTIR right from the journal’s inception. He did so in the form of providing highly valued advice on strategic issues – such as our transformation towards an open-access e-journal in 2005; and also as a dedicated referee of papers submitted to EJTIR. As a referee, Piet showed a very clear eye for the (lack of) quality and relevance of papers, and always delivered his review reports well before the deadline.